Analysis The Student Perception of Application Clinical Skills Online Learning in The Pandemic Time Covid-19 - Anik Puji Rahayu; Sulistiyawati Sulistiyawati; Cicih Bhakti Purnamasari; Endang Sawitri; Ika Fikriah (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Government policies that apply social distancing, work from home, and learn from home to prevent the spread of the Covid-19 corona virus have an impact on learning methods. Clinical learning methods in pre-pandemic health education are carried out in campus laboratories and direct clinical services to patients. Thus, in this condition, the provision cannot be implemented.